Towards to fair trade with item validation using Bloom Filters and Smart Contracts - Reis, Matheus Cunha; Sendin, Ivan da Silva (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2020)
Smart Contracts bring a new set of possibilities in the secure protocol development: participants gain guarantees of the correct execution of the protocol steps. In contrast, current Smart Contract solutions do not provide data privacy, this scenario is particularly bad in the commerce of e-goods. In this work, we present a fair trade protocol based Smart Contract and Bloom Filter for the problem of e-goods trading where the involved parts do not trust each other.